Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
Australia's large external deficits appear sustainable. There are, however, risks associated with the resulting external debt that need continued careful management. These deficits, which largely reflect high investment rather than low saving, should be sustainable as long as the Australian economy, especially its exports, grow strongly. The associated accumulation of foreign liabilities nonetheless leaves the country exposed to shocks, but these risks appear to be well managed. Australia's fiscal policy appears to be broadly consistent with guidelines for fiscal management in the face of commodity price swings.